A escrita por e-mail : influências do interlocutor e do gênero discursivo - Thom, Wilsilene Rodrigues (2007)
Research underscores the Arts student's text production in a foreign language (FL) and intends to be a contribution in teacher's training studies. Interest in the subject matter occurred as from discussions in the Research group "Interaction and Writing in Teaching and Learning" (UEM/CNPq - www.escrita.uem.br) and as a consequence of a former research which current author had been undertaking with 4th year undergraduates of the Arts Course at the State University of Maringá, Maringá PR Brazil. Research is based on the theoretical works of Bakhtin (1997; 2003) and Vygotsky (1988) and on the social and interaction theory which deals with language and the teaching of language from the social and historical point of view. Specific aims comprised (a) discussion on e-mail text production in the context of FL writing by the English Language undergraduate student; (b) the manner computer-lead interaction is reflected in FL texts by students. Data collection was undertaken during eight months and was divided into a structural period and a social and interaction one. The occurrence of both was due to the researcher?s social condition as a subject within the interaction process which underwent transformations during research. The interlocutor and gender were highlighted in data analysis, or rather, the former was due to the importance in establishing new social positions through interaction; the latter was due to the possibility of using primary gender in writing, and thus making dialogue possible. Results showed that there was an improvement both in the researchers and in the student since, as interlocutors, both formed new social positions beyond the teacher-student condition. In the case of gender, informality, a consequence of orality, provided the participating student with an opportunity of developing a naturalness in her manner of expressing herself in English.